The Girlhood of Shakespeare's Sisters Gender, Transgression, Adolescence - Higginbotham, Jennifer (Edinburgh Critical Studies in Renaissance Culture, 2013)
The first sustained study of girls and girlhood in early modern literature and culture. Jennifer Higginbotham makes a persuasive case for a paradigm shift in our current conceptions of the early modern sex-gender system. She challenges the widespread assumption that the category of the 'girl' played little or no role in the construction of gender in early modern English culture. And she demonstrates that girl characters appeared in a variety of texts, from female infants in Shakespeare's late romances to little children in Tudor interludes to adult 'roaring girls' in city comedies. This monograph provides the first book-length study of the way the literature and drama of the sixteenth and seventeenth centuries constructed the category of the 'girl'.